2019
DOI: 10.1016/j.vas.2018.09.003
|View full text |Cite|
|
Sign up to set email alerts
|

Mixed tumors of the canine mammary glands: Evaluation of prognostic factors, treatment, and overall survival

Abstract: Highlights Mixed tumors are common lesions in female dogs and present variable biological behavior. Carcinomas in mixed tumors are neoplasms that present good biological behavior. Even at an advanced stage, female dogs with carcinomas in mixed tumors exhibit a longer survival compared with bitches with carcinosarcomas. Female dogs with carcinosarcomas undergoing surgery only presented a lower overall survival rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 32 publications
(49 reference statements)
3
30
1
7
Order By: Relevance
“…Canadas et al (2018) found that, of 144 tumors, the most frequent type was complex carcinoma (49/144). For Nunes et al (2019), 75% (682/904) of the cases were carcinoma in a mixed tumor, which corroborates this study. In addition, other histological types were found, however in lesser number when compared to carcinoma in a mixed tumor.…”
Section: Discussionsupporting
confidence: 90%
“…Canadas et al (2018) found that, of 144 tumors, the most frequent type was complex carcinoma (49/144). For Nunes et al (2019), 75% (682/904) of the cases were carcinoma in a mixed tumor, which corroborates this study. In addition, other histological types were found, however in lesser number when compared to carcinoma in a mixed tumor.…”
Section: Discussionsupporting
confidence: 90%
“…Mammary gland tumors are one of the most common cancers in dogs, especially in non-spayed females, and are still one of the leading causes of death among canines [1][2][3]. Interestingly, canine mammary tumors are an attractive and useful model for studying human breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Mixed mammary carcinosarcoma is an uncommon type of neoplasm in the animals because of consist malignant of differentiated cells and aggressive behaviour (Nunes et al, 2019). It has a high vascularisation sustains the abnormal proliferative cells to receive nutrition (Gal et al, 2008).…”
Section: Introductionmentioning
confidence: 99%